FLUCTUATION-INDUCED KERR EFFECT IN CHIRAL SMECTIC-A LIQUID CRYSTAL PHASE - Andika Fajar (Jurnal Sains Materi Indonesia, 2007)
FLUCTUATION-INDUCED KERR EFFECT IN CHIRAL SMECTIC-A LIQUID CRYSTAL PHASE. The second-order electrooptic responses under large orientational fluctuations in a chiral smectic-A liquid crystal phase has been studied theoretically. The formula for analyzing the frequency dispersion of Kerr effect considering the fluctuations has been derived. The possibility of the nonlinear electrooptic response observing the soft mode condensation inducing the smectic-Cα* phase in the smectic-A phase by using the fluctuation-induced Kerr effect has been explored.